Strategi Coping Mahasiswa dalam Menghadapi Burnout Akademik - Noor Afy Shovmayanti; Nur Budi Sholekhah; Dani Kurniawan (Universitas Muhammadiyah Klaten, 2026)
Academic burnout is a phenomenon that is increasingly experienced by students as academic demands in higher education increase. Pressures such as heavy workloads, tight deadlines, academic achievement demands, and difficulties in understanding lecture material can trigger physical, emotional, and mental fatigue in students. This condition has the potential to reduce learning motivation and concentration, as well as impact students' psychological well-being if not managed properly. Therefore, students need to have appropriate coping strategies to deal with the academic pressure they experience. This study aims to identify the coping strategies used by students at Muhammadiyah University Klaten in dealing with academic burnout, as well as to understand how these strategies are applied according to the conditions faced. This study uses a descriptive qualitative approach with data collection through an open questionnaire based on Google Forms. The research subjects consisted of eight students in their 3rd and 5th semesters who were selected based on their experiences in dealing with academic pressure. Data analysis was performed using thematic analysis with reference to Lazarus and Folkman's coping theory. The results showed that academic burnout was triggered by several main factors, namely excessive academic workload, close deadlines, difficulty in understanding lecture material, and limited time management skills. In dealing with these conditions, students applied various coping strategies, including problem-focused coping, emotion-focused coping, and avoidance coping. In addition, social support from friends, family, and the surrounding environment also played a role in helping students reduce their academic stress levels. This study confirms that the coping strategies used by students are situational and tailored to the characteristics of the stressors and the conditions of each individual.